LED lights in the in vitro multiplication of three banana cultivars (2018)
Light emitting diodes (LEDs) are considered the most promising new source of light for the in vitro cultivation of plants because they have a long list of benefits and positively affect the growth of explants. The objective of this study was to evaluate the use of LEDs as an alternative light source, using fluorescent lamps in the multiplication of three banana cultivars. The Grande Naine, FHIA 18 and Prata Anã cultivars were placed in an MS (Murashige and Skoog) medium with 30 g L-1 sucrose, 100 mg L-1 myo-inositol, 7 g L-1 agar and 6 mg L-1 BAP; three successive subcultures were carried out for 30 days under five light sources (blue-EDEB LEDs 3LA1 470 nm, green-TEDS LEDs 3LA1 530 nm, red-EDER LEDs 3LA3 630 nm, Growlux fluorescent lamps and white fluorescent lamps), with a 16 hour photoperiod, temperature of 25±2°C and light intensity of 20 µmol m-2 s-1. The design was completely randomized with a 5×3 factorial (light source × cultivar), with five repetitions. For all three cultivars, it was observed that the number of shoots and leaves was not influenced by the type of light. The highest number of formed shoots was obtained with the cultivar Grande Naine (2.6 buds/explant), with no difference between cv. FHIA 18 and Prata Anã (1.4 and 1.3 shoots/explant). There was a significant difference between the cultivars and light source for the length of budding; the longest length was obtained with Prata Anã, grown under green LEDs.